In vitro evaluation of marginal leakage in bonded restorations, with mechanical or chemical-mechanical (Carisolv) removal of carious tissue Avaliação in vitro da infiltração marginal em restaurações adesivas, com remoção mecânica ou químico-mecânica (Carisolv) do tecido cariado - Ricardo Coelho Okida; Thiago Marchi Martins; André Luiz Fraga Briso (Sociedade Brasileira de Pesquisa Odontológica, 2007)
This study carried out an in vitro evaluation and comparison of the occurrence of marginal leakage in bonded restorations using mechanical or chemical-mechanical (Carisolv) removal of carious tissue. For that purpose, 40 extracted decayed human molars were divided into 4 groups: GI (burs + Prime & Bond NT + TPH), GII (Carisolv + Prime & Bond NT + TPH), GIII (burs + SBMP + Z100) and GIV (Carisolv + SBMP + Z100). After accomplishment of the restorations and thermal cycling, the teeth were exposed to dye, sectioned and qualitatively evaluated. The results demonstrated that the system of removal of carious tissue did not influence the results of microleakage at any of the cavity margins. At dentinal margins, use of the Prime & Bond NT + TPH restorative system allowed the occurrence of less microleakage than the SBMP + Z100 system. Este estudo avaliou e comparou in vitro a ocorrência da infiltração marginal em restaurações adesivas, com a utilização de remoção mecânica e químico-mecânica do tecido cariado. Para a proposição, 40 dentes molares humanos extraídos cariados foram divididos em quatro grupos: GI (brocas + Prime & Bond NT + TPH), GII (Carisolv + Prime & Bond NT + TPH), GIII (brocas + SBMP + Z100) e GIV (Carisolv + SBMP + Z100). Após a execução das restaurações e termociclagem, os dentes foram expostos a corante, seccionados e avaliados qualitativamente. Os resultados demonstraram que o sistema de remoção de tecido cariado não influenciou a ocorrência de microinfiltração em quaisquer margens cavitárias. Nas margens dentinárias, a utilização do sistema restaurador Prime & Bond NT + TPH demonstrou menor ocorrência de microinfiltração do que o sistema SBMP + Z100.